FEM study of a steel corrugated web plate girder subjected to fire - Sokołowski, Damian; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main aim of this work is a computational nonlinear analysis of a high strength steel corrugated-web plate girder with a very detailed and realistic mesh including vertical ribs, all the fillet welds and supporting areas. The analysis is carried out to verify mechanical structural response under transient fire temperature conditions accounting for an efficiency and accuracy of three various transient coupled thermo-elastic models.
Keywords: steel structures; Finite Element Method (FEM); corrugated web plate girders; fire simulation